Potential drug–drug interactions among prescriptions for elderly patients in primary health care - (:unkn) unknown (My University, 2022)
Background/aim: Elderly patients are at high risk from drug–drug interactions (DDIs). This study evaluates the potential DDIs in Turkish elderly patients at a primary health care outpatient clinic. Materials and methods: Online database systems were used to examine DDIs on the prescriptions of patients (n = 1206). The clinical severity of DDIs was classified by the Lexi-Interact Online database. Results: Of the 5059 prescriptions, 33% were found to have DDIs. We detected 29 (0.9%) A, 380 (11.8%) B, 2494 (77.7%) C, 289 (9%) D, and 18 (0.6%) X risk rating category DDIs among the prescriptions. Prescriptions of female patients and patients aged between 65 and 72 years showed significantly higher number of DDIs. The frequency of DDIs increased both with the number of drugs and combined preparations per prescription. Acetylsalicylic acid and salbutamol were the most frequently prescribed drugs contributing to clinically important DDIs. Additionally, acetylsalicylic acid and escitalopram, which interact with each other, were found on the list of Beers criteria. The most predicted clinical outcomes of DDIs were increase in therapeutic efficacy and adverse/toxic reactions. Conclusions: Prediction of DDIs in elderly patients will provide better prescribing and drug safety. Use of nonsteroidal anti-inflammatory agents, selective serotonin reuptake inhibitors, and beta-2 adrenergic receptor agonists should be closely monitored.